Analysis of Aggressive Actions in Pencak Silat Athletes Jayakarta Championship 3 - Denada Wulandari; Aridhotul Haqiyah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The objective of this study was to ascertain the extent of aggression exhibited by pencak silat athletes Jayakarta Championship 3 during competitive matches. The instrument utilized in this study was adapted from an aggression questionnaire comprising 40 questions. The results of the validity test indicated that 34 items were deemed to be valid. The data collection process involved a total of 98 athletes. The data analysis was conducted using SPSS Version 25. The findings of this study suggest that 56 athletes (57.1%) demonstrated low levels of aggression on the Physical Hostile Aggression sub-indicator, while 42 athletes (42.9%) were classified as exhibiting high levels. In the Verbal Hostile Aggression sub-indicator, 50 athletes (51%) were classified as having low aggression levels, while 48 athletes (49%) were classified as having high aggression levels. In the Physical Instrumental Aggression sub-indicator, 46 athletes (46.9%) were classified as having low aggression levels, while 52 athletes (53.1%) were classified as having high aggression levels. In the sub-indicator of Verbal Instrumental Aggression, 45 athletes were classified as low, constituting 45.9% of the sample, while the remaining 53 athletes were classified as high, representing 54.1% of the sample. A significant degree of instrumental aggression was observed among athletes participating in the Jayakarta Championship 3.